Embrace green marketing or lose competitive advantage - Sinothando Tshuma (Economics, Management and Sustainability)
The rise of the green revolution has shaken many firms to decide on their dominance or face the wrath of natural extinction by failure to adapt to changes in the macro environment. Green marketing has recently gained acceptance in the commercial world to the level that firms that still embrace the old conventional marketing paradigm are rethinking their marketing strategies. Green marketing seeks to ensure that businesses do not harm the environment they operate in or harm the planet earth's living species. There has been a dynamic shift in the marketing mix elements as organisations thrive to satisfy the needs of a chameleon consumer. The research was informed by Ottman’s paradigm shift from conventional marketing to green marketing. The study sought to determine the impact of green marketing strategies on firm performance and the challenges faced by small to medium enterprises in their quest to adopt green marketing strategies. A quantitative research design was adopted with a sample size of 20 steel and aluminum foundry firms. The primary research findings were that firms are aware of green marketing strategies and their impact on firm performance, although they face challenges in implementing them. The paper's results will help various small to medium enterprises in the foundry industry to rethink, redesign and re-engage to achieve innovation and industrialisation in a green economy.